Uma abordagem baseada em aspectos e composição dinâmica para a construção de aplicações adaptativas cientes ao contexto - Santos, Isanio Lopes Araújo (2008)
Ubiquitous computing systems operate in environments where the available resources significantly change during the system operation, thus requiring adaptive and context aware mechanisms to sense changes in the environment and adapt to new execution contexts. Motivated by this requirement, a framework for developing and executing adaptive context aware applications is proposed. The PACCA framework employs aspect-oriented techniques to modularize the adaptive behavior and to keep apart the application logic from this behavior. PACCA uses abstract aspect concept to provide flexibility by addition of new adaptive concerns that extend the abstract aspect. Furthermore, PACCA has a default aspect model that considers habitual adaptive concerns in ubiquitous applications. It exploits the synergy between aspect-orientation and dynamic composition to achieve context-aware adaptation, guided by predefined policies and aim to allow software modules on demand load making possible better use of mobile devices and yours limited resources. A Development Process for the ubiquitous applications conception is also proposed and presents a set of activities that guide adaptive context-aware developer. Finally, a quantitative study evaluates the approach based on aspects and dynamic composition for the construction of ubiquitous applications based in metrics